SYNTHESIS, SPECTRAL CHARACTERIZATION AND DNA BINDING PROPERTIES OF DINUCLEAR NICKEL (II) COMPLEXES WITH PYRIDINE BASED HYDRAZONES - D. NAGAKAVITHA,; K. HUSSAIN REDDY, (International Journal of Pharma and Bio Sciences, 2014)
Dinuclear nickel(II) complexes of functionalized heterocyclic hydrazones, viz. 2-acetylpyridine acetoylhydrazone (APAH), 2-acetylpyridine benzoyllhydrazone (APBH), 2-benzoyllpyridine acetoylhydrazone (BPAH), 2-benzoylpyridine benzoyl hydrazone (BPBH) have been synthesized and characterized on the basis of elemental analysis, molar conductivity measurements, magnetic susceptibility, electronic and infrared spectral data. Electrolytic nature of complexes is investigated by conductivity studies. IR spectral data suggest that the ligands act as neutral trifunctional NNO-donor system. Electronic spectral data suggest octahedral geometry for the complexes. Electrochemical behavior of metal complexes indicated quasi-reversible one electron reduction. DNA binding properties of complexes are investigated using UV- visible spectroscopy. Absorption titration studies revealed that these complexes bind to calf-thymus DNA strongly through intercalation involving a strong π -stacking interaction between the aromatic chromophore (pyridine moiety) and base pairs of DNA.